A Review of Adult Obesity Prevalence, Trends, Risk Factors, and Epidemiologic Methods in Kuwait - Stalo Karageorgi; Osama Alsmadi; Kazem Behbehani (Journal of Obesity)
Objective. Kuwait is among the countries with the highest obesity rates worldwide; however, little is known about the state of obesity epidemiology research in Kuwait. In this paper, we therefore review the findings and methodology of studies on the prevalence, trends and risk factors of obesity in Kuwait. Methods. The PubMed database was searched using the keyword combination: obesity and adults and Kuwait. Out of 111 articles, 39 remained after abstract review, and 18 were selected after full-text review. Results. The studies were all cross-sectional and published in the last fifteen years (1997–2012). The sample size ranged from 177 to 38,611 individuals. Only 30% of studies used random sampling. The prevalence (BMI ≥ 30) in studies with a nationally representative sample ranged from 24% to 48% overall and in adults >50 years was greater than 52%. Rates were significantly higher in women than those in men. Studies that examined trends showed an increase in obesity prevalence between 1980 and 2009. Multiple risk factors including sociocultural factors were investigated in the studies; however, factors were only crudely assessed. Conclusion. There is a need for future studies, particularly surveillance surveys and prospective cohort studies utilizing advanced methods, to monitor trends and to comprehensively assess the factors contributing to the obesity epidemic in Kuwait.